EVALUATING PRODUCT ATTRIBUTES OF ASUS LAPTOP BY USING IMPORTANCE AND PERFORMANCE ANALYSIS - Sepang, Kevin .; Lambey, Linda .; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: This research was held in Manado as a developing city in Indonesia. The populations in this research are all the buyer Asus laptop in Manado with sample size of this research is 100 respondents. Importance and Performance Analysis were used to analyze the twelve indicators in this research. The results of this research show Durability is located in quadrant I â€œConcentrate Hereâ€ (high importance, low performance), Quality, Convenience, Appropriateness, Good fit, and Easy of Care are located in quadrant II â€œKeep up the good workâ€(high importance, high performance), Price, Color, Attractiveness and Style are located in quadrant III â€œLow Priorityâ€(low importance, low performance), and Fashion and Brand Name are located in quadrant IV â€œPossible Overkillâ€(low importance, high performance). the company of laptop Asus should be maintain the durability of battery life so the consumer can used the laptop longer and make more color options, make the new style of the laptop, and the price of laptop is affordable so the consumer attracted to buy laptop Asus.Â ÂÂKeywords: product attributes, asus laptop, importance and performance analysis